1999
DOI: 10.1093/ajcn/70.5.896
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of selenium requirements for New Zealanders

Abstract: An upper estimated requirement of 90 microgram Se/d was calculated as the intake necessary for maximization of plasma GSHPx activity, as used in the derivation of the US recommended daily allowance. Our lower estimated requirement of 39 microgram Se/d was the intake necessary to reach two-thirds of maximal GSHPx activity, as was used in calculating the World Health Organization normative requirement. The lower estimate is a realistic goal for New Zealand but the upper estimate could be achieved only with regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
168
5
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(191 citation statements)
references
References 33 publications
11
168
5
7
Order By: Relevance
“…Studies indicate that serum selenium concentrations of around 1.1 mmol/l are associated with maximum activity and concentration of plasma selenoproteins (Hill et al, 1996;Duffield et al, 1999), while a serum concentration of around 1.5 mmol/l has been suggested as desirable because it may be optimal for cancer protection (Combs, 2001;Thomson 2004). Nearly 40% of the elderly women in our study exhibited a low selenium status (below 1.1 mmol/l) and more than 90% did not reach the desirable selenium level of 1.5 mmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that serum selenium concentrations of around 1.1 mmol/l are associated with maximum activity and concentration of plasma selenoproteins (Hill et al, 1996;Duffield et al, 1999), while a serum concentration of around 1.5 mmol/l has been suggested as desirable because it may be optimal for cancer protection (Combs, 2001;Thomson 2004). Nearly 40% of the elderly women in our study exhibited a low selenium status (below 1.1 mmol/l) and more than 90% did not reach the desirable selenium level of 1.5 mmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…Mean intake levels in a number of countries (Combs, 2001;Rayman, 2004) are shown in Fig. 1, which also indicates the range of Se intake believed to be required for optimal activity of plasma GPx (Thomson et al 1993;Duffield et al 1999). It is clear that the level of intake in Europe and some parts of China is not adequate for full expression of GPx.…”
Section: Selenium Intakes and Status Of Adults In Different Countriesmentioning
confidence: 99%
“…In one such study (Schrauzer et al 1977), inverse correlations were observed between apparent dietary Se intakes estimated from food-consumption data in twenty-seven (Combs, 2001;Rayman 2004) and the range of selenium intake believed to be required for optimal activity of plasma glutathione peroxidase (Thomson et al 1993, Duffield et al 1999K).…”
Section: Geographical (Ecological) Studiesmentioning
confidence: 99%
“…Selenium plasma levels for maximal glutathione peroxidase activity have been reported over the range 90-114 mg/l (Alfthan et al, 1991;Thomson et al, 1993;Duffield et al, 1999), whereas maximum selenoprotein P concentrations are reached around 83-118 mg/l (Marchaluk et al, 1995;Duffield et al, 1999), but may be as low as 71 mg/l in individuals with low selenium status (Hill et al, 1996). Rayman (1997) suggested a value of 100 mg/l as a threshold for nutritional adequacy although it has even been proposed that around 120 mg/l is a useful target for minimizing cancer risk (Combs, 2001).…”
Section: Introductionmentioning
confidence: 99%